Perbedaan Reaksi Pasar terhadap Pelantikan Presiden dan Wakil Presiden Negara Indonesia Tahun 2019 - Paramartha Daisuke Matsuzawa, Gede; Mediatrix Ratna Sari, Maria (E-Jurnal Akuntansi; Vol 30 No 10 (2020)DO - 10.24843/EJA.2020.v30.i10.p06, 2020)
This research is an event study that aims to determine the market reaction arising from the inauguration of the president and vice president of Indonesia in 2019, against companies listed in the LQ45 stock sector on October 20, 2019, using the abnormal return indicator. Statistical tests used to test hypotheses are descriptive statistical tests, normality tests and paired sample t-test. The result of paired sample t-test on abnormal return is that there is no significant difference, which means the market does not respond to the event. These results indicate that the efficient market is not answered in the event of inducting the president and vice president of Indonesia in 2019 due to the absence of abnormal returns in it. Keywords: Event Study; Market Reaction; Abnormal Return; President Election 2019.